AN ANALYSIS OF THE ROLE OF HOPE IN THE QUARTER LIFE CRISIS IN EARLY ADULTHOOD - Nurul Adharina; Karjuniwati Karjuniwati; Asysyifa Urrahmah; Safrilsyah Safrilsyah; Siti Hajar Sri Hidayati (State Islamic University (UIN) Ar-Raniry, 2022)
Early adulthood will experience stress, insecurity, worry, and social pressure regarding life goals, including students, which is called a quarter-life crisis. One factor that affects the quarter-life crisis is hope. This study aims to analyze the relationship of hope with the quarter-life crisis in early adulthood. This study uses a quantitative approach. The measuring instrument in this study uses a quarter-life crisis scale based on Robbins and Wilner's theory and a hope scale based on Snyder's theory. The sample amounted to 330 early adult students. Sampling using non-probability sampling method with purposive sampling technique. The hypothesis of this study was tested using Pearson's product-moment correlation. The study results showed a correlation coefficient (rxy = -0.249) with p = 0.000 (p ˂ 0.05), namely there is a very significant negative relationship between hope and quarter-life crisis in early adulthood, so the hypothesis is accepted. The higher the level of hope in individuals, the lower the level of quarter-life crisis experienced, and vice versa, the lower the hope, the higher the quarter-life crisis experienced by individuals.